2002
DOI: 10.7326/0003-4819-137-1-200207020-00008
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Osteonecrosis of the Femoral Head in HIV-Infected Adults

Abstract: Patients infected with HIV have an unexpectedly high occurrence of osteonecrosis of the hip. Although screening asymptomatic patients is not warranted, HIV-infected patients with persistent groin or hip pain should be evaluated for this debilitating complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
114
1
11

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(129 citation statements)
references
References 38 publications
3
114
1
11
Order By: Relevance
“…Hip has been identified as the most frequent location of osteonecrosis, and the prevalence was estimated as around 4% by MRI. 18 One subject with RA who had been excluded from the study experienced remission of arthritic symptoms and immunosuppression because of HIV infection. After receiving 3 years of HAART regimen, she had relapse of RA with joint pain and repeated Baker's cyst formation.…”
Section: Discussionmentioning
confidence: 99%
“…Hip has been identified as the most frequent location of osteonecrosis, and the prevalence was estimated as around 4% by MRI. 18 One subject with RA who had been excluded from the study experienced remission of arthritic symptoms and immunosuppression because of HIV infection. After receiving 3 years of HAART regimen, she had relapse of RA with joint pain and repeated Baker's cyst formation.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous treatment algorithms have been proposed to provide guidance to the treating physician [18,19,45,58,64], controversy remains surrounding the most appropriate surgery and at what stage of the disease process these procedures should be performed [9,10,34,50,59,60].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have attempted to identify risk factors related to these bone disorders [15]. Hyperlipidaemia, lipodystrophy, diabetes and vasculitis have been described as conditions associated with, or related to, bone disorders [16][17][18] and some risk factors have been suggested, such as alcohol abuse, smoking, hyperlactataemia and corticosteroid use [16,[19][20][21][22][23]. It has also been suggested that bone loss could be the consequence of HIV infection itself [7,11,24,25].…”
Section: Introductionmentioning
confidence: 99%